Immune Reconstitution Inflammatory Syndrome Secondary to Autoimmune Hemolytic Anemia and Cryptococcal Meningitis - Yin, SiJia; Xu, Yan; Huang, Jinsha; Xiong, Nian; Han, Chao; Ma, Kai; Guo, Xing Fang; Xia, Yun; Wan, Fang; Kou, Liang; Sun, Yadi; Wu, Jiawei; et al. (Frontiers in Neurology, 2019)
A 47-year-old HIV-seronegative woman with autoimmune hemolytic anemia (AIHA) was treated with corticosteroids for 8 months. She developed central nervous system dysfunction and was diagnosed with cryptococcal meningitis (CM) after detecting cryptococcus neoformans in the cerebrospinal fluid. The patient's clinical symptoms were worsened and unusual MRI findings of white matter lesions were noticed even after adequate treatment, which were quite unusual compared with typical characteristics of CM. This led us to carry out further investigations. Similar cases have been reported previously in published literature. Combined with clinical symptoms and MRI findings, the most likely diagnosis was Cryptococcal Meningitis-Immune Reconstitution Inflammatory Syndrome. Unfortunately, the patient deteriorated and died of respiratory failure. Cryptococcal Meningitis-Immune Reconstitution Inflammatory Syndrome may have MRI changes during the early onset of the disease (bilateral basal ganglia). We propose that close monitoring of the condition, meticulous MRI follow-up and brain biopsies should be indicated in such cases for treating them actively, so as to avoid worsening of the patients' condition.